Design of Prototype Hybrid Solar and Wind Power Electric Boat - Juliangga, Reza (Universitas Medan Area, 2024)
Design of hybrid Solar and Wind Power Electric Boat powered by a 12V DC motor prototype. In the initial stage of the project, technical drawings of the Electric boat were drawn using Sketch Up software. In the technical drawings, the positions of all important components such as solar panels, wind turbines, and batteries on the boat are shown. In the next stage, the design of a battery charging system will follow. ATMega 8535 microcontroller is used as a ‘brain’ to select the higher DC input voltage from either solar or wind energy. After the design of the battery charging system has been completed, the hardware will be installed on a small-scale Electric Boat similarly as in the technical drawing, with previously calculated specifications 1 5Watt 12V photovoltaic and 12V 1.2aH battery. In the final stage, the prototype will be tested to assess the efficiency of the battery charging system using ATMega 8535 microcontroller, with delay reads 1 second and an accuracy of 98% reading. Condition of the battery is also stable enough to provide a load on the motor with an average of 9.8 V. The boat can also move steadily even though the movement Slow speed.